(untitled) (Scientific journal of the Fergana State University, 2024)
By the 19th century, there are a number of great representatives of English literature, which reached its peak with its critical realism. By studying their work, not only the real life and lifestyle of this period, but also the set of expressive means of Victorian literature, the realistic system of storytelling, symbolism and metaphor , we will have the opportunity to learn about theatrical elements, parodies, satires, pantomimes. George Eliot, who is considered one of the great representatives of the Victorian era, is one of the prolific writers who, in his works, described the social structure of the nineteenth century and strongly criticized it, as well as fighting for the lifestyle, dignity, place and rights of women in England. Through this article, it is possible to get acquainted with the work of the English writer